The Influence Of Profitability, Goodcorporate Governance And Audit Qualityon Tax Avoidance In Pharmacy Companieslisted On The Indonesian Stock Exchange - Duma Megaria Elisabeth; Simanjuntak, Wesly Andri; Nadapdap, Kristanty M N; Saragih, Rintan Br; Gultom, Rustri Ningsih (Program Studi Akuntansi Universitas Simalungun, 2024)
The aim of this research is to test and analyze the influence of profitability, good corporate governance and audit quality on tax avoidance in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018 –2022. The population of this research is 11 sample companies. The sampling method used was purposive sampling, so that 10 pharmaceutical companies were obtained.The data used in this research are financial reports (annual reports) from companies which can be accessed via the Indonesia Stock Exchange website. The data analysis technique used is a quantitative technique. The results of this research show that partially profitability, good corporate governance have a significant effect on tax avoidance, audit quality does not have a significant effect on tax avoidance. Simultaneously, the independent variables, namely profitability, good corporate governance and audit quality, have 34.0% influence on tax avoidance and 66.0% are influenced by other factors. For this reason, the author suggests that the population in the next study can be replaced with other industries and add independent research variables in future research